2006
DOI: 10.1111/j.1075-122x.2006.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for Accurate Measurement of Invasive Breast Cancer Tumor Size

Abstract: Accurate presurgical assessment of tumor size is important for choosing appropriate treatment, especially with the increasing use of neoadjuvant and minimally invasive therapy. Breast sonography is increasingly used by breast surgeons as a part of their basic clinical evaluation. We undertook this study to compare clinical evaluation, mammography, and breast sonography for evaluating breast tumor size. A prospective analysis of 124 consecutive patients with palpable breast cancer was performed. Tumor masses be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 14 publications
2
41
0
1
Order By: Relevance
“…There are different ways to estimate tumour size, physical examination, mammography and ultra sonography are common methods, and many studies have indicated that measurement by ultrasonography is the most accurate way (9,19,20,21), e.g. Hieken TJ et.al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different ways to estimate tumour size, physical examination, mammography and ultra sonography are common methods, and many studies have indicated that measurement by ultrasonography is the most accurate way (9,19,20,21), e.g. Hieken TJ et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Shoma A et.al showed in a study involving 162 patients that it was common to overestimate the tumour size during clinical examination (19).…”
Section: Discussionmentioning
confidence: 99%
“…Selecting patients for breast conservation is primarily based on the perceived size of the tumour on preoperative radiology, which has frequently been shown to be unreliable in determining extent of disease. [4][5][6][7] The results of this study on a cohort of patients who had invasive ductal carcinoma demonstrate that reporting the relative quantity of accompanying DCIS in core biopsy specimens is of considerable value in identifying patients most at risk of compromised margins. Patients with invasive ductal carcinoma and minimal DCIS in their core biopsy had a 23% risk of compromised margins compared to a 39% risk if a DCIS component of at least 5% was present in the core biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Attempting to gauge size of lesion preoperatively has been shown to be prone to error, with under-and overestimates of disease extent. [4][5][6][7] Additional means of identifying those at high risk of compromised margins would be valuable in aiding the precision of patient selection for breast conservation or may identify patients who would benefit from wider margins at the time of initial operation.…”
mentioning
confidence: 99%
“…This finding is consistent with prior studies (Table 1). 1,3,6,[12][13][14][15][16][17][18][19][20][21] Tumour size measured by micro-CT correlated better with histopathological invasive tumour size than any of the three pre-operative imaging modalities. This is likely because micro-CT generates higher resolution images, making fine structures, anatomic features and tumour boundaries more clearly visible.…”
Section: Discussionmentioning
confidence: 99%